Management of Cancer-Associated Intestinal Obstruction in the Final Year of Life. Issue 2 (April 2020) - Merchant, Shaila J.; Brogly, Susan B.; Booth, Christopher M.; Goldie, Craig; Peng, Yingwei; Nanji, Sulaiman; Patel, Sunil V.; Lajkosz, Katherine; Baxter, Nancy N.
Background: There is variation in the clinical management of intestinal obstruction (IO) in patients with cancer. We describe the management of cancer-associated IO near the end of life in a population-based cohort with universal health coverage. Methods: Patients who died of gastric, colorectal, ovarian, and pancreatic cancers from 2002 to 2015 were identified from the Ontario Cancer Registry. Those with ≥1 hospital admission for IO in the final year of life were identified from administrative data. Management of IO at index admission was categorized as surgery, gastrostomy, stent, feeding jejunostomy, and medical management. Trends in management over the study period were assessed by the Cochran-Armitage test. Results: The cohort included 57 378 patients (gastric [n = 7448, 13%], colorectal [n = 30 577 53%], ovarian [n = 6273, 11%], and pancreatic [n = 13 080, 23%] cancers). Of those, 7618 (13%) patients had ≥1 admission for IO in the final year of life. Of these patients, 2657 (35%) patients were managed with a surgical/procedural intervention at index admission (surgery [86%], gastrostomy [8%], stent [6%], and jejunostomy [0.4%]); the remaining patients (n = 4961, 65%) received medical management. Over the study period, there was a small but statistically significant increase in the use of stents (0% in 2002 to 5% in 2015, P < .0001) and gastrostomy tubes (2% in 2002 to 4% in 2015, P = .002) and a large decrease in the use of surgery (41% in 2002 to 28% in 2015, P = .04). Conclusions: Management of IO has changed over time with the increased use of stents and gastrostomy tubes and decreased use of surgery.